Unique Contribution of Haptoglobin and Haptoglobin Genotype in Aneurysmal Subarachnoid Hemorrhage - Blackburn, Spiros L.; Kumar, Peeyush T.; McBride, Devin; Zeineddine, Hussein A.; Leclerc, Jenna; Choi, H. Alex; Dash, Pramod K.; Grotta, James; Aronowski, Jaroslaw; Cardenas, Jessica C.; Doré, Sylvain (Frontiers in Physiology, 2018)
Survivors of cerebral aneurysm rupture are at risk for significant morbidity and neurological deficits. Much of this is related to the effects of blood in the subarachnoid space which induces an inflammatory cascade with numerous downstream consequences. Recent clinical trials have not been able to reduce the toxic effects of free hemoglobin or improve clinical outcome. One reason for this may be the inability to identify patients at high risk for neurologic decline. Recently, haptoglobin genotype has been identified as a pertinent factor in diabetes, sickle cell, and cardiovascular disease, with the Hp 2-2 genotype contributing to increased complications. Haptoglobin is a protein synthesized by the liver that binds free hemoglobin following red blood cell lysis, and in doing so, prevents hemoglobin induced toxicity and facilitates clearance. Clinical studies in patients with subarachnoid hemorrhage indicate that Hp 2-2 patients may be a high-risk group for hemorrhage related complications and poor outcome. We review the relevance of haptoglobin in subarachnoid hemorrhage and discuss the effects of genotype and expression levels on the known mechanisms of early brain injury and cerebral ischemia after aneurysm rupture. A better understanding of haptoglobin and its role in preventing hemoglobin related toxicity should lead to novel therapeutic avenues.